The Changes in the Household Income of Coastal Communities on the Utilization of Caulerpa racemosa Sea Grapes in North Bintan Area Bintan District Kepulauan Riau Province - Jeri Kurnia Putra; Firman Nugroho; Viktor Amrifo (Berkala Perikanan Terubuk, 2022)
This research was conducted in June 2021 in North Bintan Area Bintan District Kepulauan Riau Province. The location of this study was determined purposively with the consideration that North Bintan area is a sub-district where most of the people work as users of caulerpa racemosa sea grapes. Determination of respondents in this study was carried out by census and using a mixed approach (mix methods). The data was collected by means of observation, documentation and direct interviews with 7 users of caulerpa racemosa sea grapes. The results of this study indicate that the household income of the coastal community of North Bintan area after becoming a sea grapes user has increased by an average of IDR 1,209,924.00 or 34%. Meanwhile, based on the analysis of the Sustainable Livelihood Framework, it shows that the business of utilizing caulerpa racemosa sea grapes is classified as sustainable from the human resources aspect, financial aspect, production aspect and marketing aspect